Enhanced photoelectrochemical protection of 304 stainless steel induced by the internal electric field effect of a g-C3N4/graphene/TiO2 Z-scheme system. (August 2023) - Zhang, Weiwei; Tao, Xianchao; Guo, Hanlin; Ding, Jianxu; Sun, Haiqing; Zhan, Xiaoyuan
Highlights: A g-C3 N4 /graphene/TiO2 Z-scheme system was constructed by hydrothermal method. A giant internal electric field formed in the heterosemiconductor junction. The Z-scheme system facilitates electron transfer and photogenerated protection. Abstract: Photo-generated cathodic protection by TiO2 -based semiconductors has attracted considerable attentions for non-sacrificial and environment-friendly characteristics. A ternary g-C3 N4 /graphene/TiO2 composite was constructed by a one-step hydrothermal method in the work. The 2D nanosheets and the TiO2 nanoparticles are closely coexisting with each other to form a wrapping structure. An internal electric field formed in the heterosemiconductor junction for matched band structure and insufficient oxidation ability of g-C3 N4 . This resulted that the electrons transfer in a Z-scheme mechanism, which was confirmed by Mott-Schottky and EIS analysis. The Z-scheme system pushed photo-excited electrons to a high energy potential that boosted electron migration from photoelectrode to the connected metal, leading to novel photoelectrochemical performance and enhanced photoelectrochemical corrosion protection of 304 stainless steel. Graphical abstract: Image, graphical abstract